(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Diabetes mellitus is a metabolic disease characterized by elevated blood glucose levels. It is brought on by either insufficient insulin synthesis or insulin resistance. Controlling the enormous rise in this disorder’s prevalence requires a safe and natural treatment. Body weight, insulin resistance, and the pro-inflammatory state of the host can all be impacted by the intestinal microbiota. Diabetes has been linked to alterations in the gut microbiome. The gut barrier’s ability to function depends on the activity of the microbiota, and its alteration is thought to be a threat factor for the low-grade inflammation linked to insulin resistance. When prebiotics are consumed to alter the gut microbiota, the body produces microbial metabolites like short-chain fatty acids, which are crucial for lowering blood sugar, reducing inflammation, justifying insulin resistance, and encouraging the release of glucagon-like peptide 1 in the host. Prebiotics can be produced artificially or come from naturally occurring sources of nondigestible carbohydrates. Current research on the potential effects of microbial metabolites and the gut microbiota on host metabolism to support health were included in this review. We presented data from multiple researches that demonstrate the potential of prebiotic ingestion to improve host physiology, change the composition of gut microbiota, and enhance gut microbial metabolism and functions in order to mitigate diabetes. This systematic review aims to evaluate the evidence surrounding the use of prebiotics in the management of diabetes, with a focus on their effects on glucose control, insulin sensitivity, and gut microbiota modulation. The review summarizes randomized controlled trials (RCTs), observational studies, and mechanistic studies to assess the potential role of prebiotics in improving metabolic outcomes in individuals with diabetes.